Freeze-dried powder from ginger slices (Zingiber officinale roscoe var. Hawaiian) - Pablo, Antonio Emmanuel S.
Powdered ginger was developed from fresh and mature Hawaiian ginger by the process of freeze-drying. Three kinds of temperature programs were followed with the objective determining the one that would give the shortest freeze-drying time. The temperature program of freezing to 40°C then drying to 80°C and lowering the drying temperature to 60°C after 8 hours, came out with the shortest freeze-drying time of 14.5 hours. Sensory evaluation tests showed that the color, aroma and flavor qualities of the powder from that temperature program was similar to fresh, unprocessed ginger. One and two week old ginger was freeze-dried to determine the effect of raw material storage on the freeze-dried powder. Sensory tests showed that ginger stored for one week before freeze-drying did not have any deteriotative effects on the color, aroma and flavor characteristics of the powdered product. Two methods of packaging were also studied, namely, packing of the powder in air and under vacuum. The packaging were also studied, namely, packing of the powder in air and other vacuum. The packaging material used was a cello-polyethylene laminate. Results of the sensory evaluation showed that packing under vacuum was able to maximize shelf-life for three months while packing in air was able to maximize shelf-life for only one month.